WHY DOES CURSING MAKE LAUGH? A PSYCHOLOGICAL APPROACH - Emre, Yusuf; Subaşı, Zeliha (My University, 2024)
Swearing is considered as an unwelcome act since it is deemed impolite to society. However, it is seen that the behaviour swearing has become pravelent in human life. What functions do the taboo words serve in an individual’s life? If swearing is merely an expression of aggression, how and why can it make people laugh? This study aims to understand why the act of swearing produced from taboo words is perceived as amusing by focusing on the relationship between profanity and humor. In this context, it is aimed to determine the role of swearing in human behavior by trying to answer the question of how taboo words are acquired during the developmental process. In addition, the study addresses the functions of swearing in an individual’s life and interactions with others aiming to understand the motivations behind the use of words prohibited by society. Finally, the question of why some swear words are perceived as humorous has been explored through the common denominators between swearing and humor. It was found that swear words serve various functions in human life, one which is generating absurdity and thus opening the door to humor. Subsequently, the study explains the conditions and mechanisms under which an aggressive act such as swearing serves the purpose of entertainment.
Keywords: Psychology; Humor; Swearing; Taboo Words; Funny